GAMBARAN DARAH PETANI YANG TERCEMAR PESTISIDA - Dewi Yudiana Shinta (EcoNews, 2019)
Many of the environmental pollution caused by the use of chemical pesticides. According to WHO, the pesticides used in the world as much as 3.5 million tons per year with the kind of high toxicity from developing countries such as Indonesia. The number of registered pesticides formula in Indonesia keeps increasing from year 1996 as much as 520 formula until 2015 as much 3,459 formula (Perveen,2011). The impact of pesticide contamination can be seen by measuring levels of the enzyme cholinesterase in the blood farmers. The purpose of the study to gauge the level of toxicity from pesticide usage by farmers by measuring levels of cholinesterase in the blood farmers and long usage of pesticides used by farmers. The benefits of this research to be able to provide information for farmers from the impact of the use of pesticides which do not use APD. This type of research is a descriptive experimental.This research was conducted on farmers in the area of Solok of West Sumatra with a simple random method of as many as 10 people. Data collection with the interview questionnaire and the wear measurement of levels of Cholinesterase in blood Cholinesterase Test Kit Livibond with AF267. The results showed that of the 10 samples examined 50% experiencing mild poisoning with levels of 62.5% Cholinesterase with a working period of 20 to 30 years, while the remaining >75% Cholinesterase levels are normal (default values are categorized decrease in AChE in Indonesia) and 10-15 year working period. Acute severe pesticide poisoning causes sufferers tounconscious, seizures, even death. chronic toxicity is more difficult to detect because it is not immediately felt, but in the long run can cause health problems.